Analisis Peran Model Pembelajaran, Kreativitas Guru, dan Kompetensi Guru Terhadap Motor Educability Test di Kelas Inklusi SD Kota Salatiga - Mochammad Alban Javier; Cahyo Yuwono (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
This study aims to analyze the role of learning models, teacher creativity, and teacher competence on motor educability test results in inclusive elementary schools in Salatiga City. This research used a mixed-methods approach with a concurrent design, combining quantitative and qualitative data. The research subjects consisted of four PJOK teachers and 91 fourth-grade students from four inclusive elementary schools in Salatiga. Data were collected through questionnaires, interviews, observations, documentation, and Motor Educability Tests using the Iowa Brace Test. Quantitative data were analyzed using descriptive statistics, while qualitative data were used to strengthen the interpretation of findings. The results showed that the implementation of learning models, teacher creativity, and teacher competence in inclusive physical education was mostly in the moderate category (50%), with some teachers categorized as high (25%) and low (25%). Meanwhile, the results of the Motor Educability Test indicated that all students (100%) were in the high category. These findings indicate that adaptive learning models, teacher creativity in modifying learning activities, and adequate teacher competence contribute to improving students' motor learning abilities in inclusive classes. The study confirms that inclusive physical education can effectively support motor skill development when supported by appropriate pedagogical strategies.